2021
DOI: 10.1038/s41467-021-22933-3
|View full text |Cite
|
Sign up to set email alerts
|

Aortic disease in Marfan syndrome is caused by overactivation of sGC-PRKG signaling by NO

Abstract: Thoracic aortic aneurysm, as occurs in Marfan syndrome, is generally asymptomatic until dissection or rupture, requiring surgical intervention as the only available treatment. Here, we show that nitric oxide (NO) signaling dysregulates actin cytoskeleton dynamics in Marfan Syndrome smooth muscle cells and that NO-donors induce Marfan-like aortopathy in wild-type mice, indicating that a marked increase in NO suffices to induce aortopathy. Levels of nitrated proteins are higher in plasma from Marfan patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 91 publications
4
24
0
Order By: Relevance
“…Attenuated TAA pathology in Fbn1 C1041G/+ ; Nox4 −/− mice provided genetic proof of ROS involvement [ 40 ]. Redondo’s laboratory reported high iNOS expression levels in the aortic media of both MFS patients and Fbn1 C1041G/+ mice [ 42 , 43 ]. Since iNOS is upregulated during oxidative stress and inflammation, this observation suggests the presence of a local pro-inflammatory state in the MFS aorta.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
See 3 more Smart Citations
“…Attenuated TAA pathology in Fbn1 C1041G/+ ; Nox4 −/− mice provided genetic proof of ROS involvement [ 40 ]. Redondo’s laboratory reported high iNOS expression levels in the aortic media of both MFS patients and Fbn1 C1041G/+ mice [ 42 , 43 ]. Since iNOS is upregulated during oxidative stress and inflammation, this observation suggests the presence of a local pro-inflammatory state in the MFS aorta.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…Since iNOS is upregulated during oxidative stress and inflammation, this observation suggests the presence of a local pro-inflammatory state in the MFS aorta. Furthermore, they showed that iNOS-derived NO drives aneurysm formation in Fbn1 C1041G/+ mice through upregulation of sGC/cGMP/PKG-I axis, and that pharmacological and/or genetic inhibition of different components of this signaling axis prevented TAA development [ 43 ]. Inhibition and even reversion of arterial disease in Fbn1 C1041G/+ mice by lentiviral mediated Prkg1 silencing greatly contrast the relatively modest attenuation of TAA pathology observed in Fbn1 C1041G/+ ; Nox4 −/− mice [ 40 , 43 ].…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to studies, half-normal synthesis of normal protein (haploinsufficiency), rather than the production of the mutant protein, could be of key importance to reach the threshold loss of fibrillin-1 function required for clinical expression of the disorder [13]. Fibrillin-1 is a key component of extracellular microfibril, which provides a scaffold for elastic fiber formation and maturation [19,20]. Therefore, mutant fibrillin-1 impairs microfibril formation, resulting in medial degeneration, which is mirrored by poor alignment of elastin filaments, altered organization of lamellar units, the accumulation of proteoglycan and vascular smooth muscle cell (VSMC) death [21].…”
Section: Cause Of Marfan's Syndromementioning
confidence: 99%